The survey of association between occupational factors and preterm childbirth - zohre Khakbazan; mehrnaze Geranmayeh; gamileh Taghizadeh; hamid Haghani (Tehran University of Medical Sciences, 2008)
Background & Aim: Socio-economical changes have increased the women;aposs opportunity to take job in recent decades. The increased levels of women in work places, has resulted in a high interest in the potential adverse effects of work on pregnancy outcome. This study was conducted in order to surveying the association between occupational factors and preterm childbirth. Methods & Materials: It is a cross-sectional study. Samples consisted of nurses and midwives (518 person) who working in Tehran;aposs universities of medical sciences hospitals. Also they delivered newborns in gestational age more than twenty weeks (term or preterm) in years 2001-2006. The subjects were selected using a multi stage sampling method. Data gathered using a self-administered questionnaire. Occupational factors labeled as fatigue score and working hours. The relation between Occupational factors and preterm birth was analyzed using descriptive and inferential statistics (Chi-squared, t-test and Mann-Whitney U test) by SPSS software. Results: Based on the study findings, the prevalence of preterm labor was 17.2% (95%CI=0.14-0.20). Although the proportions of unfavorable working conditions include: working at acute clinical wards, standing up more than 3h per each working shift, physical exercise, working in cold or hot weather, working in busy environment with continuous noise, being checker of visual and aural monitoring signals, working hours equal or more than 40 hours per week, and working fatigue score equal or more than 3 were higher in preterm group but it didn;apost show any significant relation with preterm birth. Conclusion: According to the research findings, it seems that occupational factors do not have explicit effect on preterm childbirth. Therefore more investigations are recommended.   Key words: Preterm Labor, Occupational Factors, Fatigue